Hope in suffering: an African interpretation of Jesus’ resurrection - Banda, Lameck (University of the Free State, 2010)
The research project discusses Hope in Suffering: An African Interpretation of Jesus’ Resurrection. It develops an appropriate hermeneutic for Jesus’ resurrection from the African perspective. This is because interpretation of Jesus’ resurrection remains insufficient in African theology. Generally, Africans understand Jesus’ resurrection as liberation from spiritual forces. However, this is inadequate in the African context of suffering. Hence, the research addresses the problem by developing a hermeneutic from an African perspective which provides hope in suffering. In order to understand how the resurrection has been approached in the scholarly world, chapter one surveys various interpretations of the Easter event as articulated by Bultmann, Barth, Pannenberg, Moltmann, Sobrino, Wright and Crossan. The main motif from these interpretations is that the resurrection affirms Christian faith as ultimately based on the triumph of God’s justice in the situation of suffering. However, most of these theologians neglect critical issues that affect common people in contexts of suffering. In the second chapter, it has been argued that the quest for an African interpretation of Jesus’ resurrection needs a thorough understanding of the trends and tenets of theology in Africa. Thus, African theology forms the basis on which African interpretation of Jesus’ resurrection is sought. The researcher focuses on theological trends in sub-Saharan African thinking in this pursuit of an African hermeneutic for hope in suffering. The research surveys the hermeneutical approaches to Jesus’ resurrection in Western, Latin American and African Feminist theological thoughts. The analysis of these hermeneutical approaches in the third chapter reveals that most of these approaches are actually articulated ‘from above,’ which makes them unable to address the plight of the poor and deprived in the African society. Hence, it is necessary to develop an appropriate African hermeneutic of Jesus’ resurrection which embraces an approach ‘from below’: an approach from the premise of the radical transformation of systems in society. It is further contended in the research project that African experience of suffering is the specific framework within which the interpretation of Jesus’ resurrection is sought. Therefore, chapters four and five discuss the effects of suffering on the sub-Sahara African scene. While chapter four looks at the general perspective of suffering as a hermeneutical horizon for interpreting Jesus’ resurrection, the fifth chapter gives specific portrayals of suffering in Africa. The two chapters stress that despite the nature and reality of suffering, hope of victory over the terrors of poverty, refugees and wars, and HIV/AIDS is assured in Jesus’ resurrection. The research project also discusses the biblical perspective of suffering and resurrection. What clearly comes out in the Bible is that the situations of pain and suffering lead to developing and sustaining of faith in the resurrection. The resurrection demonstrates God’s intervention in the people’s experiences of suffering. In this way, God showed that he is the God of justice who grants life and hope to the lifeless and hopeless. The sixth chapter therefore, emphasizes that despite the form through which suffering may appear in the Bible, God through the Easter event remains an ever present and powerful source of hope in suffering. In the last chapter, it is suggested that the developed African interpretation of Jesus’ resurrection in the context of suffering requires embracing specific principles of Christian spirituality and ethos, and a clear direction with specific guidelines for continued research on the subject. Above all, an African hermeneutic of Jesus’ resurrection needs to affirm that hope in suffering ultimately lies in God’s ability to transform people’s lives in Africa. Their participation in the divine process of renewal is a response to God’s work of renewal.
Thesis (Ph.D. (Dogmatology))--University of the Free State, 2010
Keywords: Jesus Christ -- Resurrection; Bible -- Black interpretations; Resurrection -- Interpretation; Spirituality -- Africa; Suffering; Hope -- Religious aspects; Hope -- Religious aspects -- Christianity